GEOELECTRIC RESISTIVITY MEASUREMENT METHOD USING A FLAT-BASE ELECTRODE - KUSUMA DEWI (NIM : 22309007), IRA
Geoelectrical method is one of geophysical methods to study the subsurface structurebased on electrical properties of the medium. Geoelctrical method is mainly applied in exploration, engineering and environmental studies. In the geoelectrical method, current is injected into the earth through current electrodes and the potential difference generated is measured at the potential electrodes. Electrodes are metal stakes that have direct contact with medium by inserting electrodes into the ground. The conventional electrodes can not be used in the environment other than ground (pavement, concrete or cement). The limitation of conventional electrodes is the rationale for doing research using flat-base electrodes as alternatives in geoelectric measurements. This study was conducted to test the flat-base electrode in determining the conductive pipe and resistive cavity using Wenner and Wenner-Schlumberger configurations. In this study the performance of flat-base electrodes is compared to conventional electrodes. Field measurements were conducted at ITB campus and in agriculture arean at Ciwaruga, representating the cases being studied. Inversion of the field data shows that conductive pipe and resistive cavity can be identified from data obtained using flat-base electrodes.